Cultura escolar e racismo: prática édagógica racial - Lovato, Glorinha (2012)
The main purpose is a comprehensive proposal to overcome racial discrimination in the school system and analyses the most common ways that racism is expressed nowadays in society. Discussions include existing stereotypes as well as the importance of using the law to fight discrimination. This involves a discussion of judicial legislation. The growing importance of education in terms of helping to achieve better living standards is explored. These include raising the quality of the teaching staff and raising the quality of the classes, as both of these actions are considered to be very useful in assuring that Afro-descendents become part of the higher education system.